Protective role of Bacopa monnieri against Rotenone- induced Parkinson’s disease in PC 12 cell lines - Gunduluru swathi,; Chintha Venkata Ramaiah,; Wudayagiri Rajendra, (International Journal of Phytomedicine, 2017)
Parkinson disease (PD) is a chronic neurodegenerative disorder characterized by the loss of dopaminergic (DA) neurons in the substantia nigra, decreased striatal dopamine (DA) levels, and consequent extrapyramidal motor dysfunction. PC 12 cells originate from pheochromocytoma cells of rat adrenal medulla and share many common characteristics with substantia nigra cells. They produce DA, several growth factors, such as nerve growth factor, fibroblast growth factor and transforming growth factor, and express DA receptors. Hence, these cells are being used to study the alterations in dopaminergic neurons, in vitro, that occur during Parkinson’s disease. Since long term usage of antiparkinsonian drugs cause high incidence of pharmacoresistence and untoward side effects, attention has been paid in recent years to screen bioactive compounds from natural medicinal plants for treatment of several neurological disorders including Parkinson’s disease. Keeping in view of relative importance of natural medicinal plants, the present study is mainly focused to characterize the anti-parkinsonian effect of Bacopa monnieri (BM), an Indian herb which is being extensively used in Ayurveda treatments related to neurological complications. The present study was designed to assess the neurotoxicity of rotenone on DA-producing PC12 cells and explore the possible antiparkinsonian effect of BM in comparing with Levodopa (LD) (Reference control). The survivability studies of PC 12 cell-lines were analysed using MTT assay. Pre-treatment with BM extract significantly ameliorated morphological damage, cell viability, and apoptosis of PC12 cells exposed to RT. Hence BM extract can be effectively used in the treatment of PD and other related neurological disorders.